The importance of institutional capacity in drinking water supply system governance: A policy evaluation from border area - Lidvina Bere Mau, Marialaeta; Sriyana, Sriyana; Purnaweni, Hartuti; Lituhayu, Dyah (Edelweiss Applied Science and Technology, 2024)
In most developing countries, the equal access to clean and potable water is a major challenge faced by many communities. This research aims to evaluate water supply system governance policies as well as potential springs, constraints and problems related to the water needs of border communities. This research is a descriptive study using a qualitative approach. The qualitative approach looks at policies, institutions, conflicts, and problems faced, as well as looking at data on water sources, socio-economic challenges, culture, and local wisdom. The research location was in Belu Regency, on the Indonesia-Leste Timor border. Research informants were representatives of local government, academics and the community. The problems faced are the underdevelopment of piped networks due to budget constraints, low capacity and quality of human resources, and the absence of specific regulations governing the Drinking Water Supply System (SPAM). The study area has springs spread across 11 subdistricts, with raw water potential ranging from 0.5 to 250 liters per second. Most of these water sources are good for community consumption, but some have not been optimally utilized so that they cannot be fully utilized to meet the needs of the population. The results show that SPAM management policies can be implemented to a certain extent, but have not yet run optimally because they still require capacity building and competence of the apparatus and local communities and an increase in the role of local governments to help implement central government policies in relation to assistance tasks and as a tool for deconcentration of the central government. In conclusion, the potential of raw water sources has not been fully utilized due to the challenges of infrastructure development and the limited capacity of human resources and budgets. Without good management and institutional support, communities will continue to face problems related to access to clean water.